Moderate Sun Exposure Is the Complementor in Insufficient Vitamin D Consumers - Wu, Shou-En; Chen, Wei-Liang (Frontiers in Nutrition, 2022)
Background and Aims Vitamin (Vit) D plays a vital role in human health, and the prevalence of Vit D deficiency worldwide has been a rising concern. This study investigates the serum 25-hydroxy-Vit D [25(OH)D] status in healthy US civilians and identifies how the two main sources, sun exposure and dietary Vit D intake, determine the final 25(OH)D levels in individuals. Methods A total of 2,360 of participants from The National Health and Nutrition Examination Survey (NHANES) 2009–2014 were analyzed. We divided the levels of sun exposure and dietary Vit D intake of all subjects into 10 strata and gave a score ranging from 1 to 10 points, respectively. Scores 1–5 in sun exposure and dietary intake were considered as relatively low exposure groups, whereas scores 6–10 were considered as relatively high exposure groups. Serum Vit D inadequacy was defined as <50 nmol/L. Linear and logistic regression analyses were used to examine the associations between sources of Vit D and serum 25(OH)D levels. Results In relatively low Vit D intake groups (Vit D intake score 1–5), relatively high sun exposure (sun exposure score >5) resulted in higher serum 25(OH)D levels (average 57 nmol/L) compared with relatively low sun exposure (sun exposure score <5) (average 50 nmol/L), whereas this difference became negligible in high intake groups (Vit D intake score 6–10). Moreover, the greatest slope occurred in the low Vit D intake curve (decile 3 of Vit D intake), which shows increased sun exposure time causing the greatest degree of change in serum 25(OH)D level in this group. Conclusion Sun exposure can significantly make up for deficiencies in subjects who consume insufficient dietary Vit D. Compared with the extra cost and time for building habits of Vit D supplementation, moderate sun exposure appears to be a simple and costless means for the public to start in daily practice.